Análisis de la pendiente de operación del relé diferencial frente a fallas trifásicas en régimen permanente, aplicado a un banco de transformadores trifásicos Yd1 - Caiza Jami, Robinson Israel (2019)
In this research a differential relay prototype was built, which it was implemented in the Electrical Engineering laboratory together with a bank of three-phase transformers and a resistive load module, whose objective is to analyze the operating pending of this relay and develop laboratory teaching practices , familiarizing students with the calibration parameters of the same. In the bank of three-phase transformers, it did the Dy1 configuration is made to feed a module of resistive balanced loads, and to obtain the currents between the primary and secondary windings of the transformer. These currents are recorded through the differential relay module that sends a signal to the protection relay, provided that the operating current I_op exceeds the minimum operating current I_dopmin, the relay acts by disconnecting the power supply system and displaying the slope graphs of the slope of each phases with their respective current values and records the time at the time the fault occurred. Finally, it developed laboratory practices where students can interact with the differential relay module by entering the operation parameters such as the pending, start current, upper limit of the graph, correction and staging factors. At the end, it did user manual and laboratory practice guides.